Assessment of Quality of Life for Patients with Permanent Pacemaker in Baghdad City - Ahmed A. Alawe, (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: To determine the (QoL) for patients with permanent pacemaker and to find-out the relationship betweenthese patients’ (QoL) and their sociodemographic characteristics such as age, gender, level of education, andoccupation.Methodology: ٨ purposive non-probability” sample of (62) patient with permanent pacemaker was involved in thisstudy. The developed questionnaire consists of (4) parts which include !.demographic data form, 2.disease-relatedinformation form, 3.socioeconomic data form, and 4.Permanent pacemaker patient’s quality of life questionnaire dataform. The validity and reliability of the questionnaire were determined through the application of a pilot study. ٨descriptive statistical analysis measures (relative frequency, percentage, mean of score) and inferential statisticalanalysis procedures (chi-square, Pearson correlation coefficient) were used for the data analysis.Results: The findings of the study indicated that the sub-domain of personal relationship as part of the socialrelationship domain of the quality of life for these individual had greatly effected at severe level what means that thebetter quality of life is in this sub-domain.The study concluded that most quality of life sub-domains of fatigue, thought, dependency on medication,independence in task management, social support, recreation and leisure, and home environment and spiritual domainwere affected at the level of not effected. That means poor quality of life related to this sub-domain.Recommendations: The study recommended that certain measures should be taken to improve quality of life forpatients with permanent pacemaker for young adult and to encourage the establishment of a society for patients withpermanent pacemaker to look after their social support and dependence on medication problem.